Using virtual robot-mediated play activities to assess cognitive skills. (18th April 2013) - Encarnação, Pedro; Alvarez, Liliana; Rios, Adriana; Maya, Catarina; Adams, Kim; Cook, Al
Abstract: Purpose : To evaluate the feasibility of using virtual robot-mediated play activities to assess cognitive skills. Method : Children with and without disabilities utilized both a physical robot and a matching virtual robot to perform the same play activities. The activities were designed such that successfully performing them is an indication of understanding of the underlying cognitive skills. Results : Participants' performance with both robots was similar when evaluated by the success rates in each of the activities. Session video analysis encompassing participants' behavioral, interaction and communication aspects revealed differences in sustained attention, visuospatial and temporal perception, and self-regulation, favoring the virtual robot. Conclusions : The study shows that virtual robots are a viable alternative to the use of physical robots for assessing children's cognitive skills, with the potential of overcoming limitations of physical robots such as cost, reliability and the need for on-site technical support. Implications for Rehabilitation: Virtual robots can provide a vehicle for children to demonstrate cognitive understanding. Virtual and physical robots can be used as augmentative manipulation tools allowing children with disabilities to actively participate in play, educational and therapeutic activities. Virtual robots have the potential of overcoming limitations of physical robots such as cost, reliability and the need for on-site technical support.